Insights and Tracking of Pollution Awareness Using Google Trends - Laico, Stephen A. (J Health Pollut, 2018)
BACKGROUND. Although pollution is the largest environmental cause of disease and premature death in the world today, it does not receive consistent and commensurate public attention. OBJECTIVES. This paper quantifies this phenomenon, tracks recent efforts, and offers strategies for improving pollution awareness. METHODS. Google Trends allows a user to compare up to five terms or topics simultaneously. Results are displayed as a set of time series. The values displayed are not the actual search counts but percentages relative to the total searches across the specified geography (worldwide, country, state/province, and city) and time period. The resulting numbers are then scaled from 0 to 100 (to create an Interest Index) based on the proportion to all searches on all terms or topics. DISCUSSION. Pollution interest can be quite different at a country level compared with the worldwide view. Predictably, pollution interest is highest in many of the countries most affected by pollution. However, many of the wealthiest countries show low interest in pollution. CONCLUSIONS. Solving any problem begins with awareness, which generates concern and understanding, followed by action. Determining what issues people are searching on provides a reliable barometer of the true interest in and awareness of an issue. Google Trends provides a mechanism to help track ongoing pollution problems and solutions. DISCLAIMER. The author serves as the Chief Technical Officer of Pure Earth. The author had no role in the review of or decision to accept this manuscript. COMPETING INTERESTS. The author declares no competing financial interests